Prevalence of long COVID-19 syndrome among health care workers of Patan Academy of Health Sciences - Pandey, Bimal; Gautam, Sanjeev; Karki, Sanjit; Lama, Mipsang; Sigdel, Keshav Raj; Hirachan, Niroj (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Any symptoms acquired after COVID-19 infection that persists beyond 12 weeks period and not explained by any other disease either already present or acquired after COVID-19 infection is termed as long COVID 19 by World Health Organisation. We tried to find out the prevalence of long COVID 19 in healthcare workers.Method: Questionnaire was made in google form based on COVID-19 Yorkshire Rehabilitation Screening Tool (COVID YRS Tool). Ethical approval was taken from IRC-PAHS. Data collected from all health care workers of PAHS from 2022/05/20 to 2022/07/20. Difference in Precovid and Postcovid status in different domains were compared by statistical tests.Result: The median age of our participants was 29 years. Prevalence of Long COVID 19 was 68.1%. 19 55.3% ha mild, 10.4% had moderate, 2.4% had severe symptoms. The most common symptom was fatigue (44%), anxiety (41%) and shortness of breath (36%). The COVID YRS Tool overall score was statically significant with p value